Perancangan Perbaikan Pembagian Beban Kerja Work Center Satori Cell Line CV. Sinar Baja Electric - Wiryamanta Suciadi; I Gede Agus Widayana (Jurnal Titra, 2022)
Division of workload is important for manufacturing companies in the ongoing production process. CV. Sinar Baja Electric, which one of the largest loudspeakers manufacturers in Indonesia doesn’t yet have standard workload share in some part of the production division. One of the divisions is the Work Center Satori Cell Line, which is a loudspeaker assembly production line with the Satori trademark. So far, the company has had difficulty in distributing a balanced workload for operators because they still do not have standard time data for each of the existing sub-operations. The division of labor is assisted by the line balancing method to get a balanced division of labor. The results of this study are the standard for all sub-operations and the distribution of operator workload at the Work Center Satori Cell Line per product type. Through the proposed improvements can increase the daily output produced. The increase occurred in assy 1 by 7.14% and 53.57% in assy 2 Satori type TX. Meanwhile, in assy 1, the MW/MR and 6.5MR types increased by 3.13% and 17.86%, respectively.